Decoding DNA sequence-driven evolution of the human brain epigenome at cellular resolution - Emre Caglayan; Genevieve Konopka (Nature Communications)
Abstract DNA-based evolutionary comparisons of regulatory genomic elements enable insight into functional changes driven in cis, partially overcoming tissue inaccessibility. Here, we harnessed adult and fetal cortex single-cell ATAC-seq datasets to uncover DNA substitutions specific to the human and human-ancestral lineages within apes. We found that fetal microglia identity is evolutionarily divergent in all lineages, whereas other cell types are conserved. Using multiomic datasets, we further identified genes linked to multiple lineage-divergent gene regulatory elements and implicated biological pathways associated with these divergent features. We also uncovered patterns of transcription factor binding site evolution across lineages and identified expansion of bHLH-PAS transcription factor targets in human-hominin lineages, and MEF2 transcription factor targets in the ape lineage. Finally, conserved features were more enriched in brain disease variants, whereas there was no distinct enrichment of brain disease variants on the human lineage compared to its ancestral lineages. Our study identifies ancestral evolutionary patterns of the human brain epigenome at cellular resolution.